A review on green supply chain management, social capital and sustainable performance - Abidin, Rahimi; Che Sobry, Suheil; Hasnan, Norlena (2018)
Nowadays, companies start to recognize green supply chain mangement as a business imperative and one of the factors to the sustainable performance of the organizations.However, in maintaining the integrity of the supply chain, it is important to build social capital among organization as the chain can be strengten by strong relationships.This paper discuss on the influence of social capital on the green supply chain management (GSCM) and sustainable performance.The study reviews past literatures related to the link between GSCM and sustainable performance, and eventually, examine the role of social capital on this linkage.The literature indicated that social capital plays significant role towards organizational‟sustainable performance.As the green supply chain itself involves cooperation and collaboration from internal and external parties, strong social capital would ensure understandings among these parties. In addition, this paper provides recommendation for future research to be conducted on this field.